The use of danaparoid to manage coagulopathy in a neurosurgical patient with heparin-induced thrombocytopenia type II and intracerebral haemorrhage - Hertle, Daniel; Hähnel, Stefan; Richter, Götz Martin; Unterberg, Andreas; Sakowitz, Oliver; Kiening, Karl (British journal of neurosurgery, 2011)
This study presents a case of bifrontal intracerebral haemorrhage in a patient with heparin-induced thrombocytopenia type II (HIT II). HIT II was induced by treatment with low-molecular-weight heparin for recurrent deep vein thrombosis caused by essential thrombocytosis and accompanied by hepatic thromboembolism. This patient was treated with platelet substitution and neurosurgical haematoma evacuation. Anticoagulation with 2500 units danaparoid per day was sufficient for therapy of thrombosis and no rebleeding occurred.
Published online: 13 Aug 2010
Gesehen am 22.09.2022